2021
DOI: 10.1111/joie.12266
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Estimating State Dependence in Consumers’ Brand Choices Applied to 762 Pharmaceutical Markets*

Abstract: This article shows how state dependence effects can be estimated for many markets and with few assumptions by using data on how the shares of consumers buying specific products differ between those who bought the same product on their latest purchase occasion and those who did not. Using information regarding which product was cheapest when consumers made their last purchases as instrument, I estimate that state dependence increases the probability that consumers will buy the product they bought the last time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Patients stick to a pharmaceutical product over longer periods. Such a behavior of state dependence is well documented for the Swedish pharmaceutical market (Granlund, 2021;Janssen, 2020). While we do not distinguish between the reasons for an initial substitution, we document a fundamental change in behavior due to the first substitution.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Patients stick to a pharmaceutical product over longer periods. Such a behavior of state dependence is well documented for the Swedish pharmaceutical market (Granlund, 2021;Janssen, 2020). While we do not distinguish between the reasons for an initial substitution, we document a fundamental change in behavior due to the first substitution.…”
Section: Discussionmentioning
confidence: 44%
“…Health economic studies in multiple countries have concluded that patients prefer originals and experience history dependence when choosing pharmaceuticals, meaning that they tend to consume products with which they have had a positive experience (Bronnenberg et al, 2015;Feng, 2020;Granlund, 2021;Janssen, 2020). 3 We add to the literature but also highlight that it is possible to break such history dependence.…”
Section: Introductionmentioning
confidence: 89%
“…Health economic studies in multiple countries have concluded that patients prefer originals and experience history dependence when choosing pharmaceuticals, meaning that they tend to consume products with which they have had a positive experience (Bronnenberg et al, 2015;Feng, 2020;Granlund, 2021;Janssen, 2020). 3 We add to the literature but also highlight that it is possible to break such history dependence.…”
Section: Introductionmentioning
confidence: 87%